PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MICROSITE UNTUK MENINGKATKAN KEMAMPUAN BERLITERASI SAINS SISWA SEKOLAH DASAR - Ginting Lestari, Ani; Suciptaningsih, Oktaviani Adhi; Pristiani, Riska (Perspektif Ilmu Pendidikan, 2025)
Based on the results released by the OECD in 2023, literacy in Indonesia has increased in rank but decreased in score. The biggest decline was in the field of science. Facts on the ground also show that students' ability in science literacy is still low. This is evidenced by data from the Regional Competency Test conducted in 2024. To overcome this, researchers try to provide alternatives in the form of developing microsite-based learning media to improve the science literacy skills of elementary school students. The research method used is R n D with the ADDIE model. The result is that microsite-based learning media to improve students' literacy skills in elementary school is feasible to use and preferred by students. With a good level of media feasibility, it is hoped that this microsite-based learning media can be used in learning and can improve the science literacy skills of elementary school students.